Colonial Rule and Political Relations between Ondo and its Neighbours, 1915-1951 - Adesote, Adesola (Al-Adab Journal, 2025)
This paper examines the impact of colonial rule on the political relations between Ondo and its neighbours between 1915 and 1951. This was a period between the First and the Second World Wars. The paper argues that the imposition of British colonial policy of administration greatly affected the precolonial peaceful coexistence and political relations between Ondo and its neighbours such as Ile-Oluji and Odigbo. Before the imposition of British colonial administration on the whole Nigeria in general, and Yorubaland in particular, each Yoruba community enjoyed political independent. It was the introduction of the so-called native administration (indirect rule) by the British that lead to the creation and imposition of Native Authority, one of the instruments of native administration over a considerable number of communities that were hitherto independent that eventually resulted in causing serious strains in the political relations among some communities in Yorubaland in general and Ondo Division in particular. The concentration of the British centralisation of political authority over the whole of Ondo districts through the use of Osemawe of Ondo, as the sole Native Authority brought an end to an interesting experiment of Native Administration in the districts as a result of various agitations.